2020
DOI: 10.4103/jcd.jcd_541_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of qualitative and quantitative remineralization potential of four different remineralizing agents in enamel using energy.dispersive X-ray: An in vitro study

Abstract: Background: The principles of minimally invasive dentistry clearly tells us the need for clinically effective measures to remineralize the early enamel caries lesions. Aims and Objectives: The aim of this study was to evaluate the remineralisation potential of four different remineralisation agents used quantitatively by surface microhardness and qualitatively by energy dispersive X ray analysis. Materials and Methods: Artificial enamel lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The intrinsic properties of Nano-HAP, such as size, chemical composition, and structural resemblance to enamel apatite, may play a key role in the remineralization process, as suggested by our study (36) . According to a study done by Hemalatha et al (37) Nano-HAP had the highest capacity for remineralization, followed by CPP-ACP; these findings were consistent with those of the current investigation.…”
Section: Discussionsupporting
confidence: 93%
“…The intrinsic properties of Nano-HAP, such as size, chemical composition, and structural resemblance to enamel apatite, may play a key role in the remineralization process, as suggested by our study (36) . According to a study done by Hemalatha et al (37) Nano-HAP had the highest capacity for remineralization, followed by CPP-ACP; these findings were consistent with those of the current investigation.…”
Section: Discussionsupporting
confidence: 93%
“…When compared with fluoride, the use of Nano HA in toothpastes, according to Amaechi et al (2019), Hemalatha et al, (2020 Khandelwal et al, (2020) and Manchery, et al, (2019), has the advantage of presenting results similar to fluoride without the risk of fluorosis. As for antimicrobial capacity, Kamath, et al (2017), Bossu et al (2019 and Ionescu, et al (2020) concluded that the use of Nano HA can inhibit biofilm adds and growth in deciduous tooth samples, which may contribute to the prevention, stagnation, and control of caries disease.…”
Section: Nano Hydroxyapatitementioning
confidence: 99%
“…Net mineral loss from a broken balance between demineralization and remineralization causes dental caries, which is an infectious multifactorial disease [ 87 , 88 ]. Conventional strategies for dental hard tissue restoration include the mechanical removal of decay and filling with artificial materials [ 89 ].…”
Section: Application Of Nano-cs In Dental Hard Tissue Remineralizationmentioning
confidence: 99%